Moderating usability tests : principles and practices for interacting - Dumas, Joseph S., 1943- (Morgan Kaufmann series in interactive technologies., 2008)
Many aspects of usability testing have been thoroughly studied and documented. This isn't true, however, of the details of interacting with the test participants who provide the critical usability data. This omission has meant that there have been no training materials and no principles from which new moderators can learn how to interact. Moderating Usability Tests is the place for new and experienced moderators to learn about the rules and practices for interacting that have never been described in one place before. Authors Dumas and Loring draw on their combined 40 years of usability testing experience to develop and present the most effective principles and practices - both practical and ethical --for moderating successful usability tests. To help usability professionals, students, and novices understand these principles, the authors provide videos from their lab that demonstrate good and poor interaction as well as commentary from a panel of testing experts on why certain techniques succeed or fail. The videos are accessible from the publisher's companion web site. . Presents the ten "golden rules" that maximize every session's value . Offers targeted advice on how to maintain objectivity . Discusses the ethical considerations that apply in all usability testing . Explains how to reduce the stress that participants often feel . Considers the special requirements of remote usability testing . Demonstrates good and bad moderating techniques with laboratory videos accessible from the publisher's companion web site